Analisis Kebutuhan Pengembangan Mini Book Berdasarkan Kronologi pada Materi Asal Usul Nenek Moyang Indonesia untuk SMA - Sugarda, Tasya Mutia; Hastuti, Hera (Lembaga Yasin AlSys, 2024)
In the world of education, a teacher is able to know the feasibility and practicality of teaching materials in which there is learning material. So that the material delivered to students can be received properly. Teachers are also asked to be more creative in delivering material, one way is the existence of additional media as teaching materials, namely Mini Book. With the Mini Book, it can make it easier for teachers to deliver material. The advantages of this Mini Book can help students to think chronologically in historical material, this teaching material media can help students in sorting time and knowing historical events according to facts. In the purpose of this research process is to find out the needs analysis of Mini Book development as a support for historical learning media in high school, which is in accordance with the independent curriculum. In conducting the research process, is very necassary to know what methods to use. One of them uses tallyhe research and development method or what cam be called (R&D) which uses the ADDIE model. However, in this research stage, it is only carried out limited to the needs analysis stage, which at this stage of the process the researcher uses data collection techniques in the form of observation and questionnaire filling. Therefore, the results of this stage can be seen in three ways, namely: (1) Describing the needs of students, which requires innovative media that can make it easier for students to understand the material. (2) Analyzing what is needed by the teacher, one of which is that the teacher needs supporting media that can facilitate the delivery of material practically. (3) Studying teaching materials that are in accordance with the independent curriculum.